Creativity Specialization: Does Diversity in Creative Skills Matter in Team Innovation?. (April 2023) - Baruah, Jonali; Burch, Gerald F.; Burch, Jana J.
This comprehensive study investigates the role of diverse creativity relevant traits in collaborative innovation. An initial screening with 301 participants evaluated everyone's dominant creativity skill. In a subsequent session, 50 teams based on their dominant creativity skill participated in a creative idea-generation and selection task either in a homogeneous (all specialized in same creativity domain) or in diverse-skill (each member with unique creativity domain) group. As hypothesized, the diverse-skill groups generated more ideas than the homogeneous original, fluent, and flexible thinkers but not from elaborate thinkers groups. The diverse-skill groups also outperformed the homogeneous original thinkers groups in the originality of ideas generated. Elaboration of ideas mediated the relationship between the quantity and the quality of ideas in both generation and selection phases. The current study extends creativity research by highlighting the importance of a multidimensional approach to creativity in a collaborative context that is controversial in the current literature.